The Role of Transesophageal Echocardiography in the Intraoperative Period - Gouveia, Veronica; Marcelino, Paulo; A. Reuter, Daniel (Current Cardiology Reviews, 2011)
The goal of hemodynamic monitoring and management during major surgery is to guarantee adequate organ perfusion, a major prerequisite for adequate tissue oxygenation and thus, end-organ function. Further, hemodynamic monitoring should serve to prevent, detect, and to effectively guide treatment of potentially life-threatening hemodynamic events, such as severe hypovolemia due to hemorrhage, or cardiac failure. The ideal monitoring device does not exist, but some conditions must be met: it should be easy and operator-independently to use; it should provide adequate, reproducible information in real time. In this review we discuss in particular the role of intraoperative use of transesophageal echocardiography (TOE). Although TOE has gained special relevance in cardiac surgery, its role in major non cardiac surgery is still to be determined. We particularly focus on its ability to provide measurements of cardiac output (CO), and its role to guide fluid therapy. Within the last decade, concepts oriented on optimizing stroke volume and cardiac output mainly by fluid administration and guided by continuous monitoring of cardiac output or so called functional parameters of cardiac preload gained particular attention. Although they are potentially linked to an increased amount of fluid infusion, recent data give evidence that such pre-emptive concepts of hemodynamic optimization result in a decrease in morbidity and mortality. As TOE allows a real time direct visualization of cardiac structures, other potentially important advantages of its use also outside the cardiac surgery operation room can be postulated, namely the ability to evaluate the anatomical and functional integrity of the left and the right heart chambers. Finally, a practical approach to TOE monitoring is presented, based on a local experience.
Keywords: hemodynamic monitoring